Changes in the etiology of candidiasis: analysis of the detection frequency of Candida spp. among patients with inflammatory respiratory diseases in the Kharkiv region, Ukraine (2019–2021) - Shevchenko, Yuliya; Golubka, Olha; Bolshakova , Halyna; Chastii, Tetyana; Minukhin, Valery; Kuchma, Iryna; Zhuravlyova , Iryna; Savinova, Tetyana (Annals of Mechnikov’s Institute, 2026)
In clinical practice, invasive mycoses are becoming increasingly important due to the increase in morbidity in the world, the rapid spread of resistant strains and a critical shortage of new antifungal drugs. The leading etiological role in the development of mycotic infections belongs to fungi of the genus Candida, among which the species Candida albicans remains traditionally dominant, however, the epidemiological picture of candidiasis is gradually changing due to the increase in the proportion of the Candida non-albicans group in mycotic pathology. The aim of this study was to study the prevalence and species structure of clinically significant isolates of Candida spp. circulating among patients with inflammatory diseases of the respiratory tract - residents of the city of Kharkiv and the Kharkiv community (Ukraine). Materials and methods. Over a three-year observation period (from 2019 to 2021), the authors conducted a microbiological study of clinical material (samples from the oropharyngeal mucosa) from 1,150 people with inflammatory diseases of the respiratory tract. Laboratory diagnostics included a standard set of mycological methods, and final identification and testing for antifungal susceptibility were performed using the automated Vitek2 Compact system. Results and discussion. The results obtained indicate an increasing persistence of Candida spp. in the observation groups from 3.7% in 2019, to 4% in 2020 and 5.7% in 2021. In the non-albicans group, the species Candida krusei dominated – 6.9%, other Candida species were isolated significantly less frequently: C. glabrata, C. tropicalis, C. kefyr – 4.3%, 3.4%, 2.6%, respectively. The susceptibility profile of the recovered isolates to itraconazole, fluconazole and voriconazole was studied: Candida non-albicans strains demonstrated increased resistance to itraconazole (42.8%) and voriconazole (57.2%), while C. albicans isolates were characterized by higher levels of fluconazole resistance (31.6%). Analysis of the obtained results allows predicting a further increase in infectious complications caused by Candida among patients with inflammatory processes of the respiratory tract, which may require mandatory laboratory monitoring and correction of therapeutic treatment in order to prevent the occurrence of invasive candidiasis.